The budding tree : - Kitahara, Aiko (Dalkey Archive Press, 2008)
Japanese author Kitahara depicts in these six tales the plight of single women struggling for success in early-to-mid-19th-century Japan. These young women protagonists are gifted artists or fledgling entrepreneurs who have lost the protection of men, either by the death of fathers or divorce from husbands, and dare to make a name on their own, often with dire consequences. In the title story, owner Okaji is struggling to keep her new restaurant, Moegi (the budding tree), afloat despite a famine and competition from her ex-husband's more established restaurant. In Love's Chill Wind, a schoolteacher resolves to maintain a school her deceased father founded. Moreover, these proto-feminists have to fend off pesky matchmakers and importunate advances by hardly well-meaning suitors, such as the married man in Innocent in Love, who seduces out of spite his childhood friend, now a successful designer of ornamental hairpins. Kitahara also elegantly portrays the dilemma of the young Oichi in Forget-Me-Not, who must make a painful compromise in love for the sake of her art. The timeless conflicts of Kitahara's characters will resonate with today's readers